Produção do cuidado em um centro de atenção psicossocial I do semiárido paraibano - Miranda, Lívia Maria Tavares (2023)
The Psychosocial Care Centers (CAPS), in their different modalities, represent strategic points of attention within the Psychosocial Care Network (RAPS). These are open and community health services, made up of multidisciplinary teams that adopt an interdisciplinary approach. They prioritize care for people with serious and persistent mental disorders, as well as those facing suffering or mental disorders in general. The evaluation processes acquired a political function through the reformulation of the care model, serving as an instrument to enhance practices that replace the hospital-centric model. Thus, the dissertation's general objective is to analyze the care practices and work process in the CAPS in the city of Queimadas-PB, through evaluation and monitoring indicators. This is an evaluative research, with a quantitative approach, in which the use of 16 CAPS monitoring, evaluation and management indicators were analyzed, subdivided into eight themes: Attention to Crisis Situations, Qualification of Group Care, Networking, CAPS Management, Permanent Education, Singularization of Care, Use of Medication, Care for People with Intellectual Disabilities, with a time frame of 2022. The data were analyzed using descriptive statistics, using the Excel program, with measures of central tendency and dispersion. The results showed that in the first indicator Care for crisis situations, an average of 40.9% of referrals to patients in crisis was obtained, in the second indicator Care for the family of the patient in crisis, an average of 41.5% was obtained, in the third indicator points out Participation in family groups, ranging from 3.8% to 23.0%, the qualification of group services, in the first quarter the percentage was 25%, in the second 44.4%, in the third 42.9 % and in the fourth quarter 50%, in the Formulation of singular therapeutic projects, varied from 13.1% to 17.5%, the indicator Systematic Review of Singular Therapeutic Project in the team varied between 2.7% to 12.9%, the indicator Number of cases per university professional reference, varied between 63 and 89 cases per university professionals, the shared Singular Therapeutic Project indicator, varied between 8.1% and 16.5%, the indicator of higher education human resources, 18,388.8 hours were obtained per 100,000 inhabitants, the indicator of Investment in Permanent Education Actions, observing an average of 138 hours per year, which corresponds to 0.8%, the indicator Insertion of people with Intellectual Disabilities in Therapeutic Residential Services , presented an insertion of 75%. It is concluded that the effective application of the indicators developed can promote the strengthening of the evaluation culture, improving both the CAPS and the evaluation instruments themselves. More than allowing comparison with different realities, this evaluative culture can directly contribute to the continuous qualification of services.